Upaya Meningkatkan Hasil Belajar Matematika dengan Metode Resitasi pada Materi Bangun Datar Siswa Kelas VII SMP Teknologi Pilar Bangsa Tangerang - Yupiter Carlis Gulo (Universitas Indraprasta PGRI, 2018)
This research aims to improve the teaching and learning process and improve the results of learning math on the material flat-wake up with the method resides of Class VII JUNIOR HIGH Technology nation's pillars of Tangerang. This type of research is qualitative research i.e. Research action class (PTK), the learning model used was the model MC Taggart and Kemmis. The application of this method is done in the III cycle. Cycle I gained an average rating of 57 students. cycle II obtained an average score of 65 students. Cycle III average student gained 81. A summary of this research is to study with the method resides was able to improve the results of student learning and fun for students.